Backbone FCH⋅⋅⋅O Hydrogen Bonds in 2′F‐Substituted Nucleic Acids1. Issue 46 (23rd September 2013) - Martin‐Pintado, Nerea; Deleavey, Glen F.; Portella, Guillem; Campos‐Olivas, Ramón; Orozco, Modesto; Damha, Masad J.; González, Carlos
<x xml:space="preserve">Abstract</x> Polarizing CH⋅⋅⋅O hydrogen bonds: The structure of oligonucleotides containing alternating and contiguous tracts of 2′F‐RNA and 2′F‐ANA nucleotides reveals that nonconventional FCH⋅⋅⋅O hydrogen bonds have a strong stabilizing effect on 2′‐fluorinated duplexes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>